Relationship between transfer of technology skills, human resource development skills and work performance of Malaysian Cocoa Board extension agent in Sarawak, Malaysia - Abd Halim, Nur Syahirah (2020)
This study was conducted to evaluate the work performance of extension agent in transfer of technology based on the perceptions of cocoa farmers. Extension agents play important role in transferring the technology to the farmers; thus extension agent should be competent in performing the duty. Extension agent of Malaysia Cocoa Board (MCB) Sarawak need to improve their competency in transfer the technology to the farmers so that the productivity of the cocoa plantation could be improved. The objective of the study; i) to determine the perception of cocoa farmers on level skills of extension agents in Transfer of Technology (ToT) skills, Human Resource Development (HRD) skills and Work performance. ii) to evaluate the relationship between ToT skills and HRD skills with work performance. iii) to determine skills that contribute the most towards the work performance of extension agents in Sarawak. The ToT skills needed by extension agents are technology skill, delivering skill and evaluating skill and HRD skills need by extension agents are leadership skill, help in making decision skill and social skill. This research employed Model of Iceberg by Spencer & Spencer (1993) as this model often use in determining the work performance of the individual. This study focuses on the visible part of the Iceberg Model which is knowledge and skill. Stratified random sampling employed in this study with 148 respondents of productive cocoa farmers selected to evaluate extension agent performance through structured questionnaire. Strata sampling was used in this study as are regional offices which were Kota Samarahan and Betong. Collected questionnaires were analysed using the correlational analysis to determine the relationship and multiple regression analysis for identification which skills contributed the most. Descriptive analysis was used to collect demographic information of respondents and level determination. Results revealed that the level of extension agents in all skills were high as perceived by productive cocoa farmers. Based on the findings, positive relationships found between ToT skills and HRD skills with work performance. Multiple regression was conducted to determine the skills that contributed to the work performance of extension agents. Help in making decision skill, social skill and technology skill have significant values < 0.05. The adjusted r square reported was 0.772. Technology skill help in making decision skill and social skill contribute the most towards the work performance of extension agents in MCB Sarawak. Help in making decision skill, social skill and technology skill explained about 77% of the variance of work performance of MCB extension agents in Sarawak. ToT skills and HRD skills are very important to be viewed by organisations to improve the performance of the individual. Based on the result, it shows that extension agents were not competent enough as perceived by the productive cocoa farmers. This research should be conducted in qualitative approach either from the extension agents' perceptive or upper management perceptive. MCB and other agency of agriculture should evaluate the knowledge and skill of extension agents from time to time for continuous performance in their work.